Rare bird documentation form for Greater Scaup at Princeton, 1979 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1979)
Rare bird documentation form for twenty Greater Scaups at Princeton in Scott County, IA on March 10, 1979. Epson - sheet feed